Chloride Ingress in Cement Mortars Exposed to Acidithiobacillus thiooxidans Bacteria - Onesmus Mulwa Munyao; Joseph Karanja Thiong’o; Jackson Muthengia Wachira; Daniel Karanja Mutitu; Genson Murithi; Romano Mwirichia (Advances in Materials Science and Engineering)
Concrete structures placed in aggressive aqueous environments are vulnerable to degradation. Majority of studies have linked structural failures to the ingress of deleterious ions into the cement matrix. Some microbial activities may accelerate the penetration of harmful materials into the cement matrix and hence cause pronounced deterioration. This work reports a laboratory-simulated study carried out to determine the extent of chloride ingress in cement mortars exposed to Acidithiobacillus thiooxidans. Test prisms were cast from Portland pozzolana cement (PPC) and ordinary Portland cement (OPC) with water-to-cement ratio maintained at 0.5. Acidithiobacillus thiooxidans bacterial solution of concentration 1.0×107 cell/mL was used to prepare microbial mortar prisms, whereas distilled water was used to prepare the control mortar prisms. The test prisms were subjected to porosity and accelerated chloride ingress after 28th day of curing. Compressive strength was determined after the 2nd, 7th, 28th, and 56th days of curing. Apparent diffusion coefficients (Dapp) were estimated from the solutions to Fick’s second law of diffusion. After the 56th day of curing, the microbial-treated mortars exhibited a significant reduction in compressive strength. The resultant percentage decrease in compressive strength was 30.74% and 19.88% for OPC and PPC, respectively. Further, microbial-treated mortars demonstrated both high porosity and chloride ingress as compared to the control test mortars. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses showed the formation of new deleterious products in the microbial-exposed mortars.